Efficiency of the Transport Process from the Point of View of Selected Drivers’ Activities - Kolenc, Jurij; Jakomin, Livij; Trupac, Igor; Zgonik, Miran (Promet - Traffic&Transportation, 2012)
This paper presents the results of research in the transportprocess efficiency from the point of view of driver’s activities inroad goods transp01tation, by vehicles with payload up to 5tons. Based on the expe1t assessment of 6233 transportationtasks and measuring the frequency of individual operations ofthe drive1; an analysis has been performed on the results andtheir influence on the efficiency of the transp011 process.Among the numerous activities of the driver directly related todriving a motor vehicle, those relating to the vehicle and cargobefore can-iage, in the course of can-iage and after it, this paperconcenLrates on the analysis of those activities related to loadingand discharge, the specific manoeuvres and d1iving operationsin a motor vehicle.